Current status of synthetic hemozoin adjuvant: A preliminary safety evaluation. Issue 18 (19th April 2016) - Lee, Michelle Sue Jann; Igari, Yoshikatsu; Tsukui, Toshihiro; Ishii, Ken J.; Coban, Cevayir
Highlights: Hemozoin is a by-product of Plasmodium parasites. Synthetic hemozoin (sHZ) is a potent adjuvant in vaccine formulations. Optimized sHZ adjuvant is recently produced in a GLP-certified facility. Optimized sHZ is safe, tolerable and has no toxicity in GLP non-clinical setting. Abstract: Although adjuvants are a "must-have" component of successful vaccines, there are very few adjuvants licensed for use in humans, there is therefore an urgent need to develop new and safer adjuvants. Synthetic hemozoin (sHZ), a chemical analog of hemozoin which is produced by the malaria parasite, exhibits a potent adjuvant effect which enhances antigen-specific immune responses to vaccines. The potency of sHZ adjuvanticity is not limited to malaria specific vaccines, it has also been demonstrated to be effective in influenza and dog allergy models. While the synthesis of uniformly sized sHZ with consistent characteristics has proven difficult, we have recently successfully optimized the manufacture of sHZ product with an optimal adjuvant effect. Here, we summarize recent developments on the adjuvant properties of optimized sHZ adjuvant, including its good laboratory practice (GLP) non-clinical safety profile in animals. These studies ensure the safety of optimized sHZ product to be readily used as vaccine adjuvant beforehand in veterinary medicine.